The Malaysian literature in English programme (literature in action): a position paper - Mohd Sukri, Hanna Insyirah; Norazizan, Muhammad Hafidzudeen (UiTM Cawangan Johor, 2022)
This position paper intends to explore both sides of the literature component included in Malaysian English programme in schools, specifically at the secondary level. We analyse the literature component, namely Literature in Action (LiA), in the perspective of the objectives stated in the Standard-Based English Language Curriculum (SBELC) developed by the Ministry of Education (MOE). The discussion made in the paper also revolves around the component's rationales, its drawbacks, as well as beneficial propositions to resolve the shortcomings. It could enrich future research on English literature in Malaysian classrooms and thus, contribute to the English curriculum in Malaysia.